CONSUMER PREFERENCES OF DIESEL IN THE FAXINAL SOTURNO-RS - Marzari, Dione Somavilla; Dörr, Andréa Cristina; Guse, Jaqueline Carla; Rossato, Marivane Vestena (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708779 Brazil occupies a prominent position in diesel consumption, and became self-sufficient in oil production from 2006. Several studies involving consumer behavior of diesel have been performed in the country. However, no study of this kind was held in the Faxinal Soturno/RS and region. The objective of this study is to identify the behavioral patterns of consumer consumption of diesel in the Faxinal Soturno / RS. The data used for analysis are of primary nature, obtained by applying structured forms directly to consumers of diesel in the city. The results show that the use of three types of diesel (S1800, S500 and S50) presents itself on average 300 liters per month. Diesel fuel is most commonly used by the consumer S1800 and S50, so that the S500 is less consumed. We conclude that factors such as price and recommendations of the manufactures are the key attributes valued by the interviewees in their choice.